Water Security and its role in food security - S. M. Taheri (آب و توسعه پایدار, 2023)
The inadequacy of water resources to meet the needs of food production is a very important issue that will increase in importance in the future. If local renewable water sources (in soil) and water (in rivers, lakes, reservoirs, aquifers) are sufficient to produce a reference food supply (including 3000 kcal of daily requirement, of which animal products include 20 percent) for all residents. If not, we consider a food production unit to have a lack of green-blue water. If it is not enough for all residents, we consider a food production unit to have a lack of green-blue water. The number of people living in food production units affected by green-blue water scarcity has increased from 360 million people in 1905 (21% of the world's population at that time) to 2.2 billion (34%) in 2005. During this period, the lack of green-blue water has spread to large areas and has increased in previous areas. Water security is a concept that is examined in different dimensions and aspects. Four dimensions of these cases were identified, each of which consists of two complementary aspects: direct-indirect, macro-micro, technical-political and peace-conflict. In this study, the indirect role of water on food security on a global scale was investigated using a quantitative spatial approach. Since food security is intertwined with water security in many ways, the role of water scarcity on the disruption of food production and the impact of trade on this interaction was analyzed, and while examining the relationship of social resilience with these issues, the areas that It was identified that they were facing certain challenges in this field. With this work, the concept of water security became systematic and finally related to the issues of vulnerability, resilience and sustainability.